Zebrafish as a Useful Tool in the Research of Natural Products With Potential Anxiolytic Effects - Cueto-Escobedo, Jonathan; German-Ponciano, León Jesús; Guillén-Ruiz, Gabriel; Soria-Fregozo, Cesar; Herrera-Huerta, Emma Virginia (Frontiers in Behavioral Neuroscience, 2022)
Zebrafish (Danio rerio) is a popular and valuable species used in many different biomedical research areas. The complex behavior that fish exhibit in response to different stimuli allows researchers to explore the biological and pharmacological basis of affective and mood disorders. In this sense, anxiety is commonly studied in preclinical research with animal models in rodents. During the last decade, those models have been successfully adapted to zebrafish. Stressful stimuli, such as novel environments, chemical substances, light conditions, and predator images, can trigger defensive behaviors considered indicators of an anxiety-like state. In the first stage, models were adapted and validated with different stressors and anxiolytic drugs with promising results and are now successfully used to generate scientific knowledge. In that sense, zebrafish allows several routes of administration and other methodological advantages to explore the anxiolytic effects of natural products in behavioral tests as novel tank, light-dark chamber, and black/white maze, among others. The present work will review the main findings on preclinical research using zebrafish to explore of anxiolytics effects of natural products as plant secondary metabolites such as flavonoids, alkaloids and terpenes or standardized extracts of plants, among others. Scientific literature confirms the utility of zebrafish tests to explore anxiety-like states and anxiolytic-like effects of plant secondary metabolites, which represent a useful and ethical tool in the first stages of behavioral.